Production-Distribution of Perishable Food considering Customer Time Window - Weibin Feng; Shangcheng Du; Yanli Xiao; Xiangyang Ren (Discrete Dynamics in Nature and Society)
Aiming at the production-distribution problem of perishable food, considering the interference caused by the change of the customer’s time window in actual distribution process, using the ideas of disruption management, analyzing the disturbance of the interference event to the production-distribution system, and constructing the perishable food production-distribution problem disturbance identification and disturbance measurement, and with the minimum deviation between the new scheme and the original scheme as the goal, a mathematical model of disturbance recovery is established. An improved ant colony algorithm-mixed ant colony algorithm based on the change of customer time window for perishable food production-distribution problem was designed to solve the problem. Finally, the simulation experiments are carried out by examples, and compared with the rescheduling results, the effectiveness of the disruption management model and the algorithm-mixed ant colony algorithm are also verified. The research results show that the disruption management can effectively reduce the degree of program deviation and control the cost reasonably.